Transfection of B7—1 cDNA empowers antigen presentation of blood malignant cells for activation of anti—tumor T cells - 克晓燕 贾丽萍 王晶 王德炳 (Chinese medical journal, 2003)
Ojbective To define roles of B7-1 co-stimulation factor expressed in human malignant cell lines in mediating anti-tumor T cell immune responses.Methods Examining human leucocyte antigen(HLA)and B7 expressions on 8 human blood malignancies cell lines by flow cytometry.Transtecting B7-1 gene to B7-1 negative(B7^-)Raji and B7^- Jurkat cell lines by liposome,and comparing the potencies of blood malignant cell lines in the induction of T cell activation by examination of T cell cytokine mRNAs before and after transtection using semi-quantitative reverse transcription polymerase chain reaction(RT-PCR). Results High level of HLA Ⅰ and Ⅱ molecules were expressed in most human blood malignant cell lines examined,and the co-stimulatory factor B7-2 was also highly expressed.In contrast,another member of B7 family:B7-1 was either not axpressed or very limitedly expressed in most of these hematopoietic malignant cell lines.Most importantly,transfection of B7-1 gene to B7^-.Raji and B7^-.Jurkat cell lines made these cell lines better antigen presenting cells for stimulation of anti-tumor T cell activation,which was demonstrated by up regulation of expression of T cell cytokines IL-2,IL-4 and INF-γ mRNAs after incubation of these tumor cells with T cells for 24h.Conclusions B7 co-stimulation plays an important role in anti-tumor immunity.Transfection of B7-1 gene to the human hematopoietic malignant cell lines that are deficient in the B7-1 expression empowers their antigen presentation potengy for activation of anti-tumor T cells.Our results suggested that repairing the deficiency of B7-1 co-stimulatory pathway in tumor cells might be a novel immunotherapeutic approach for human hematopoletic malignancies.